The Impact of Fatherlessness on Moral and Religious Development in 4-Year-Old Children - Annisa Roro Muzammil; Rikza Azharona Susanti (Al-Qalam Institute, 2025)
This study aims to analyze the influence of fatherlessness on the moral and religious development of 4-year-old children and explore moral and religious development in children, especially in the aspects of understanding ethical values, discipline, and introduction to religious teachings. The research is based on the importance of parenting by both parents in shaping morals from an early age. This study uses a Mixed Method approach, namely a combination of quantitative and qualitative methods. The research findings indicate that fatherlessness has a significant impact on children's moral and religious development. Children who grow up without a father tend to have difficulty internalizing moral and religious values. They are more dependent on mothers and peers in understanding social and religious norms. The results of the Two-Way ANOVA statistical test show that differences in moral and religious development between children growing up with and without a father are significant. This study recommends increasing the role of the extended family and society to replace the father's function, as well as a community-based approach to support the moral and religious development of children who experience fatherlessness.